Determining the aetiology of exudative pleural effusions in patients undergoing pleural biopsy for diagnosis at Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) - Sirriram, Sanvir (My University, 2017)
Background and objectives: The vast range of potential aetiologies of exudative pleural effusions frequently poses a diagnostic dilemma for the treating physician. It is important for the physician to have a basic knowledge of the common conditions which cause exudative pleural effusions in their setting in order to direct their investigations appropriately and cost effectively. The aims of this study were to describe the demographic profile of patients admitted for investigation of exudative pleural effusions to Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) in Johannesburg, South Africa, and to describe their aetiologies, as determined by the investigations performed. Methods: This was a retrospective record review of 162 patients with exudative pleural effusions, confirmed on pleural fluid analysis, admitted to CMJAH for investigation over a period of one year from the 1st January 2015 to the 31st December 2015. An analysis of patient demographics, HIV status, smoking status, results of investigations and the patient diagnoses were undertaken. Results: Of the 162 patients, 100 (61.7%) were male and 62 (38.3%) were female. The mean age, overall, was 44 years. With regard to HIV status, 78 (48.1%) patients were HIV-seronegative, 76 (46.9%) were HIV-seropositive and 8 (4.9%) were of unknown HIV status. HIV-seropositive patients were younger (mean age 39.2 years) than the HIV-seronegative patients (mean age 49.5 years; p <0.01). There was no difference in gender in those patients who were HIV-seropositive (p = 0.502) and racial influence could not be evaluated due to the fact that most patients were of African origin. Overall, on pleural biopsy, 45 of the patients (27.8%) were diagnosed as having tuberculosis (TB), 40 (24.7%) had bacterial empyema, 37 (22.8%) had malignancy, 29 (17.9%) had chronic pleuritis, 8 (4.8%) had an inconclusive diagnosis and 3 (1.9%) had a combined diagnosis of TB and malignancy. Amongst the HIV-seropositive patient group, the diagnoses were as follows; 26 patients had TB, 24 patients had bacterial empyema, 12 patients had chronic pleuritis, 9 patients had malignancy, 3 cases were inconclusive and a combination of both TB and malignancy was present in 2 patients. There was a higher incidence of infective aetiologies in HIV-seropositive patients. Amongst the HIV-seronegative patient group, the diagnoses were as follows; 28 patients had malignancy, 16 patients had bacterial empyema, 16 patients had chronic pleuritis, 14 patients had TB, 3 cases were inconclusive and a combination of both TB and malignancy was present in 1 patient. There was a higher incidence of malignancy in the HIV-seronegative patients. TB was predominantly found in the younger, HIV-seropositive patients (p = 0.01 and p = 0.006, respectively). Patients that were female, older patients (mean 57.5 years) and those of negative HIV status were more likely to have malignancy (p = 0.04, p = 0.01 and p = 0.006, respectively). Although there was a trend to an association between smoking status and the occurrence of malignancy (p = 0.081), this did not reach statistical significance. This could simply be a consequence of small patient numbers and it was not recorded if patients were previous smokers. The causative organisms for the bacterial empyemas found in this study included: Staphylococcus aureus, Streptococcus pneumoniae, Klebsiella pneumoniae and Pseudomonas aeruginosa. Discussion: Overall the main aetiologies of exudative pleural effusions of patients at CMJAH were TB, bacterial empyema, chronic pleuritis and malignancy. These finding were similar to studies done in other third world countries.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Internal Medicine. 2017, Johannesburg.
Keywords: Pleural Effusion